(untitled) - Tameichi Hara (New York, 1961)
In this book Captain Hara discusses how he commanded a Japanese destroyer in all of the major Pacific sea conflicts: Empress Augusta Bay, Coral Sea, the invasion of the Philippines, Guadalcanal, Savo Island, and Midway. While on a re-supply mission through Blackett Straight in August 1943, upon noticing a fire-ball explosion near the destroyer "Amagiri" in front of his destroyer "Shigure", he ordered for his ship's crew to shoot at Lt. J.F. Kennedy's sinking PT-109. He provides a most harrowing description -- as commander of cruiser Yahagi -- how he barely survied its sinking alongside the ill-fated battleship Yamato on their suicide mission to attack the U.S. forces invaiding Okinawa. He details his training of the pilots of suicide motorboats (Shinyo: "ocean shaker") that were designed to ram Allied warships approaching Japan. After I wrote to him, he sent me an autographed photograph of himself in 1968 -- a fine keepsake from one of the luckiest Japanese destroyer commanders to have survived so many desperately fought WWII sea battles. His 312-page book was published by Ballantine Books, initially in 1961.
Keywords: World war; Naval operations,Chiến tranh thế giới thứ II; 1939-1945,1939-1945; Japanese